2008
DOI: 10.1063/1.3050111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of backflow generation in nematic liquid crystals

Abstract: The mechanism of backflow generation in nematic liquid crystals under the application of an electric field is investigated by molecular dynamics simulation, and the roles of intermolecular interaction in the generation of bulk velocity are investigated. It is confirmed that the reorientation of molecules by the application of an electromagnetic field induces a transient "S-shaped" bulk velocity profile. The rotation and rearrangement of molecules during the reorientation process generate a local bulk velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The plot of bulk velocity at t * = 130 shows an S-shaped velocity profile. This confirms the generation of a bulk flow due to molecular reorientation, as demonstrated by a 2D molecular dynamics simulation [19] and simulation using macroscopic continuum approach [17] and observed in a visualization experiment [20].…”
Section: Simulation Of Backflowsupporting
confidence: 81%
See 1 more Smart Citation
“…The plot of bulk velocity at t * = 130 shows an S-shaped velocity profile. This confirms the generation of a bulk flow due to molecular reorientation, as demonstrated by a 2D molecular dynamics simulation [19] and simulation using macroscopic continuum approach [17] and observed in a visualization experiment [20].…”
Section: Simulation Of Backflowsupporting
confidence: 81%
“…For the development of microactuators and micromanipulators, the understanding of the molecular-level mechanism of backflow is essential. A study using a 2D molecular dynamics simulation [19] showed that the rotation and rearrangement of molecules under the application of an electric field introduces a local bulk velocity gradient, which plays an important role in the generation of macroscopic flow. The computed velocity profile in the 2D simulation is qualitatively in agreement with that observed in visualization experiment [20].…”
Section: Introductionmentioning
confidence: 99%
“…Translational motion is coupled to the orientational dynamics of n(r, t ). In its turn, director reorientations induce torques and forces that cause the material to flow (the so-called backflow effect [33,41,42]) and thus modify v(r, t ). The director fluctuations establish an intrinsic memory at the scales τ d < τ < τ h , which is typically much longer than the hydrodynamic memory time of the isotropic fluid [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this definition, S = 0 denotes a completely isotropic phase, whereas S = 1 a completely ordered phase . The long‐range molecular ordering in PTCDI‐C13 aggregates was analyzed by the intermolecular orientational correlation function, computed as Cr=1Ni1nirinircosθ cos φwhere N is the total number of molecules, n i (r) is the number of molecules within a distance r , and r + δr from molecule i , θ , and φ are the intermolecular angular order parameters, defining the orientation between the π cores of individual PTCDI‐C13 molecules.…”
Section: Computational Approachmentioning
confidence: 99%